RETRACTED: Impact of digital technologies on green economic growth - Valeva Katina; Nikolova-Alexieva Valentina; Terziyska Margarita (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001